Comparison of Longitudinal Changes of Cerebral Small Vessel Disease Markers and Cognitive Function Between Subcortical Vascular Mild Cognitive Impairment With and Without NOTCH3 Variant: A 5-Year Follow-Up Study - Yoon, Cindy W.; Kim, Young-Eun; Kim, Hee Jin; Ki, Chang-Seok; Lee, Hyejoo; Rha, Joung-Ho; Na, Duk L.; Seo, Sang Won (Frontiers in Neurology, 2021)
No study yet has compared the longitudinal course and prognosis between subcortical vascular cognitive impairment patients with and without genetic component. In this study, we compared the longitudinal changes in cerebral small vessel disease markers and cognitive function between subcortical vascular mild cognitive impairment (svMCI) patients with and without NOTCH3 variant [NOTCH3(+) svMCI vs. NOTCH3(-) svMCI]. We prospectively recruited patients with svMCI and screened for NOTCH3 variants by sequence analysis for mutational hotspots in the NOTCH3 gene. Patients were annually followed-up for 5 years through clinical interviews, neuropsychological tests, and brain magnetic resonance imaging. Among 63 svMCI patients, 9 (14.3%) had either known mutations or possible pathogenic variants. The linear mixed effect models showed that the NOTCH3(+) svMCI group had much greater increases in the lacune and cerebral microbleed counts than the NOTCH3(-) svMCI group. However, there were no significant differences between the two groups regarding dementia conversion rate and neuropsychological score changes over 5 years.